A Survey of Suicide by Burning in Tehran, Iran - Fakhredin Taghaddosinejad; Ardeshir Sheikhazadi; Behnam Behnoush; Jafar Reshadati; Seyed Hossein Sabery Anary (Acta Medica Iranica, 2010)
To identify the characteristics of completed suicide by burning in Tehran. A retrospective analysis of data obtained from Tehran's Legal Medicine Organization and judiciary system over 5-years (from 2002 to 2006). During the 5 years, 374 decedents (64.2% female and 35.8% male) were diagnosed as suicide by self-burning, and the annual incidence rate was 0.9 per 100,000 general population-years. The most at risk group was young females. Sixty-five decedents (17.4%) had died at the scene of incidents. The location at the time of attempted suicide in all female victims and 75.4% of male decedents was home. Sixty-one percent of decedents were married and 26.2% of them had no education. Most victims were residents of suburban areas. The annual incidence rate of self-burning suicide in Tehran was found to be lower than other Iran's geographic areas, although it was higher than developed countries. Self-burning was more frequent in females than in males and was noted mainly in young age groups' residents of suburban areas with low level of education. These characteristics suggest that social factors are the main drive leading to an unacceptably high rate of suicide by self-burning among women in Tehran.